2022
DOI: 10.3390/atmos13091450
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Pollution and Its Response to Nitrogen Dioxide Change from a Dense Ground-Based Network in the Yangtze River Delta: Implications for Ozone Abatement in Urban Agglomeration

Abstract: Understanding the response of tropospheric ozone (O3) to nitrogen dioxide (NO2) change is important for local O3 control. The relationship between O3 and NO2 at county scale in China has been extensively studied using models, but there is a lack of results from direct measurements. In this study, we used measurements of O3, NO2 and meteorological conditions from a dense network in the Yangtze River Delta (YRD), and satellite observed formaldehyde (HCHO) and NO2 column densities for the analysis of O3 variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…First, we excluded the self-reported physician-diagnosed incident cases of hypertension during follow-up. Second, we took into account the potential confounding effects of other air pollutants such as PM 2.5 and NO 2 , which have been reported to correlate with O 3 [34,35] and also affect blood pressure [36,37]. Twopollutant and three-pollutant models were then constructed by introducing one of the two pollutants from PM 2.5 and NO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we excluded the self-reported physician-diagnosed incident cases of hypertension during follow-up. Second, we took into account the potential confounding effects of other air pollutants such as PM 2.5 and NO 2 , which have been reported to correlate with O 3 [34,35] and also affect blood pressure [36,37]. Twopollutant and three-pollutant models were then constructed by introducing one of the two pollutants from PM 2.5 and NO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we excluded the self-reported physician-diagnosed incident cases of hypertension during follow-up. Second, we took into account the potential confounding effects of other air pollutants such as PM 2.5 and NO 2 , which have been reported to correlate with O 3 [ 35 , 36 ] and also affect blood pressure [ 37 , 38 ]. Two-pollutant and three-pollutant models were then constructed by introducing one of the two pollutants from PM 2.5 and NO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the reaction of NO 2 and other atmospheric substances such as volatile organic compounds (VOCs) with vapor forms secondary pollutants such as tropospheric ozone (O 3 ) and particulate matter (PM) [10]. A study by He et al [11] indicated that the O 3 concentration is sensitive to reductions in NO 2 in the megacities of China. Moreover, NO 2 can be a cause of acid rain, which causes ecosystem degradation [12,13].…”
Section: Introductionmentioning
confidence: 99%